Distribution and Population Status of Black Winged Stilt (Himantopus Himantopus) In Alaniya Dam, Kota District of Rajasthan - Mamta Nagar,; Vanita,; Smriti Johari, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Wetlands and small water lakes are important habitats for waterbirds such as ducks, geese, and swans, water hens etc. The distribution of Black-winged stilt (Himantopus himantopus)species was conducted in Alniya dam. Information on the number of sightings per visit along with a number of individuals per sighting, flock composition, and population structure (adult and Juvenile) was recorded during present study. This comprehensive analysis provides valuable insights into the dynamic population dynamics of Black-winged stilts at Alniya Dam, Kota. Such insights are crucial for understanding the species' ecological requirements and guiding conservation efforts aimed at preserving their natural habitat and ensuring their long-term survival. The results indicate fluctuations in the number of sightings and flock sizes between the first and second years of the study period. These fluctuations may reflect seasonal changes in habitat conditions, resource availability, or migratory patterns. Furthermore, the observed variations in flock composition, with the species predominantly found in small groups but occasionally forming larger flocks, suggest complex social dynamics within Black-winged Stilt populations. The presence of both adult and juvenile birds throughout the study period indicates breeding activity within the study area.
Keywords: Wetland; Threats; Breeding behaviour; Nesting; Population status